Legal Analysis of Euthanasia in Indonesia: Perspectives of Medical Ethics and the Need for Regulation - Idil Fitri; Muhamad Adystia Sunggara; Syafri Hariansyah (Green Publisher Indonesia, 2025)
Euthanasia is a highly controversial issue in Indonesia, related to the fundamental principle of the non-derogable right to life. This study aims to examine the key legal issues and the regulatory ambiguity concerning euthanasia from the perspective of medical ethics and the urgent need for regulation. The study highlights that the absence of a clear legal framework results in legal uncertainty for medical practitioners and patients seeking the right to end their suffering voluntarily. This research employs a normative juridical method to analyze the regulatory framework in Indonesia and compare it with countries that have legalized euthanasia. The study highlights the need for a comprehensive legal framework to ensure legal certainty, protect medical professionals, and uphold patients' rights while balancing the right to life and dignified death in line with Indonesia's social and cultural norms.